2015
DOI: 10.1007/s10143-015-0641-3
|View full text |Cite
|
Sign up to set email alerts
|

The start and development of epilepsy surgery in Europe: a historical review

Abstract: Epilepsy has not always been considered a brain disease, but was believed to be a demonic possession in the past. Therefore, trepanation was done not only for medical but also for religious or spiritual reasons, originating in the Neolithic period (3000 BC). The earliest documentation of trepanation for epilepsy is found in the writings of the Hippocratic Corpus and consisted mainly of just skull surgery. The transition from skull surgery to brain surgery took place in the middle of the nineteenth century when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 81 publications
0
25
0
4
Order By: Relevance
“…However, based on our results, robot-assisted SEEG electrode implantation seems more efficient, requiring less time in the operating room (see Results). Notably, children in both group 1 (robot-assisted) and group 2 (Talairach framebased) had no permanent SEEG-related complications, and they had low rates of transient SEEG-related complications (1 patient in each group had symptomatic hemorrhagic complications that were transient), which highlights the low complication rate of SEEG electrode implantation Although SEEG has been the standard of care at many European epilepsy centers since the 1950s, 5,28,29 it is now gaining popularity at epilepsy centers throughout North America. [12][13][14]24,31 Although SEEG electrode implantation techniques have been in use in North America since the 1970s, 25 advances in neuroimaging and robotics have made SEEG more accessible.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, based on our results, robot-assisted SEEG electrode implantation seems more efficient, requiring less time in the operating room (see Results). Notably, children in both group 1 (robot-assisted) and group 2 (Talairach framebased) had no permanent SEEG-related complications, and they had low rates of transient SEEG-related complications (1 patient in each group had symptomatic hemorrhagic complications that were transient), which highlights the low complication rate of SEEG electrode implantation Although SEEG has been the standard of care at many European epilepsy centers since the 1950s, 5,28,29 it is now gaining popularity at epilepsy centers throughout North America. [12][13][14]24,31 Although SEEG electrode implantation techniques have been in use in North America since the 1970s, 25 advances in neuroimaging and robotics have made SEEG more accessible.…”
Section: Discussionmentioning
confidence: 97%
“…has been used in Europe for invasive delineation of the EZ since the 1950s. 28 Numerous reports demonstrate that SEEG is a safe and effective technique for the identification of the EZ in both children and adults. 7 Recent advances in neuroimaging, stereotaxy, and robotics have reinvigorated and expanded interest in SEEG as a method for localizing the EZ, and have resulted in increased interest in SEEG at epilepsy centers around the world.…”
mentioning
confidence: 99%
“…12 One example of his observations was through his study of unilateral seizures, in which he concluded that motor movement was localizable to the cortex. 42 His description of focal motor seizures was behind the coining of the term "jacksonian epilepsy." He also believed and described an evolutionary hierarchy within the nervous system.…”
Section: Anatomy As It Relates To Functionmentioning
confidence: 99%
“…Even into the 17th and 18th centuries, epilepsy was viewed as a nervous or mental disorder rather than a neurological disease. 13 The first true surgery for epilepsy was performed in 1886 by Sir Victor Horsley and William Macewen 13 and surgery was usually for seizures secondary to trauma or tumors. Antiepileptic medications were not readily available at that time, making surgery the only recourse.…”
mentioning
confidence: 99%